U.S. History for the Gifted and Talented - Zola, John. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
The major objective of this teaching guide is to help high school classroom teachers of United States history develop and implement curriculum for gifted and talented students. Specifically, it presents objectives for gifted students in the area of social studies, offers a structure upon which discussion questions and learning activities can be based, and provides nine Learning Activity Packets (LAPs). A LAP is a module of subject-related teaching materials which move from structured questions to guided activities and finish with open-ended inquiries. LAP titles are "The History of History,""American Revolution,""Technology and Modernization,""Cultural Egotism,""Nazism,""Land Use and Culture Conflict: The American Indian vs. White Settlers,""Racism, Discrimination, & Prejudice,""War and Warfare: The Civil War," and "Foxfire." For each LAP, information is given on an overview of the topic, guiding questions, sources of further information, activities, investigative techniques, and extension activities. Students are involved in a variety of activities including compiling annotated bibliographies, writing research and position papers, discussing history-related issues in class and in small groups, defining concepts and generalizations, and preparing history classes for a lower grade. Students are expected to be highly self-directed and to use sources available in the school and community in addition to sources suggested in the unit. (DB)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academically Gifted; Curriculum; Educational Needs; Educational Objectives; Inquiry; Learning Activities; Learning Modules; Secondary Education; Social Studies; Student Role; Teacher Role; Teaching Guides; Teaching Methods; United States History; Guides, Classroom -- Teacher